PROSPEK PENGEMBANGAN TANAMAN JERUK SIAM (Citrus nobilis) BERWAWASAN AGRIBISNIS DI KECAMATAN BOLANO LAMBUNU KABUPATEN PARIGI MOUTONG - Hadayani Hadayani (Universitas Tadulako, 2009)
The research aim was to investigate the prospect of orange plant development based on agribusiness concept. The research location was purposively determined based on the reason that Bolano Lambunu Sub-District is one of orange development centers in Parigi Moutong Regency. Samples of 45 orange farmers were randomly taken from orange farmer population of 300 people. The prospect of the orange plant development was investigated using SWOT analysis. The result of the SWOT analysis showed that the orange plant farm shows promising signs of growth potential in the future as indicated by the strength factor value of 1.82 (59.1) and weakness factor value of 1.26 (40.9%) out of the IFAS matrix total score of 3.08. Meanwhile, EFAS matrix showed that the value of opportunity was 1.94 (65%) and threat score was 1.03 (35%) out of EFAS matrix total score 2.97.